The effect of the "Follow in my Green Food Steps" programme on cooking behaviours for improved iron intake: a quasi-experimental randomized community study - René Lion; Oyedunni Arulogun; Musibaau Titiloye; Dorothy Shaver; Avinish Jain; Bamsa Godwin; Myriam Sidibe; Mumuni Adejumo; Yves Rosseel; Peter Schmidt (BMC, 2018)
Abstract Background Nutritional iron deficiency is one of the leading factors for disease, disability and death. A quasi-experimental randomized community study in South-West Nigeria explored whether a branded behaviour change programme increased the use of green leafy vegetables (greens) and iron-fortified bouillon cubes in stews for improved iron intake. Methods A coinflip assigned the intervention to Ile-Ife (Intervention town). Osogbo (Control town) received no information. At baseline 602 mother-daughter pairs (daughters aged 12-18) were enrolled (Intervention: 300; Control: 302). A Food Frequency Questionnaire assessed the addition of cubes and greens to stews, the primary outcome. Secondary outcomes were the addition of cubes and greens to soups and changes in behavioural determinants measured using the Theory of Planned Behaviour. Structural Equation Modelling (SEM) evaluated the impact of the intervention on behavioural determinants and behaviour. Results The data of 527 pairs was used (Intervention: 240; Control: 287). The increase in greens added to stews was larger in the Intervention town compared to the Control town (MIntervention = 0.3 [SE = 0.03]; MControl = 0.0 [SE = 0.04], p < 0.001, r = 0.36). Change in iron-fortified cubes added to stews did not differ between towns (p = 0.07). The increase in cubes added to soups was larger in the Intervention town compared to the Control Town (MIntervention = 0.9 [SE = 0.2] vs MControl = 0.4 [SE = 0.1], p < .0001, r = 0.20). Unexpectedly, change in greens added to soups was larger in the Control town compared to the Intervention town (MIntervention = − 0.1 [SE = 0.1]; MControl = 0.5 [SE = 0.1], p = 0.003, r = 0.15). The intervention positively influenced awareness of anaemia and the determinants of behaviour in the Intervention town, with hardly any change in the Control town. Baseline SEMs could not be established, so no mediation analyses were done. Post-intervention SEMs highlighted the role of habit in cooking stews. Conclusions The behaviour change programme increased the amount of green leafy vegetables added to stews and iron-fortified cubes added to soups. Future research should assess the long-term impact and the efficacy of the programme as it is scaled up and rolled out.